Citizen Science Studies in Nursing: A Systematic Review - Carmen Torró-Pons; Carlos Saus-Ortega; María-Luisa Bal (MDPI AG, 2024)
Background: Citizen science is a research approach wherein citizens actively participate alongside professionals in some or all stages of the research process. The bidirectional benefits it generates, especially in the field of health, including empowerment, new hypotheses, and results, and addressing issues truly important to society, justify the necessity to establish a common framework and address barriers to ensure a fruitful evolution of this new approach within nursing research. The aim was to analyze nursing projects with a citizen science focus that have been conducted. Methods: PRISMA guidelines were employed to conduct a systematic review. Searches were conducted on PubMed, CINHAL, LILACS, IBECS, and Cochrane. Following the identification and screening process, 13 studies were included. The quality of the articles was assessed using the Joanna Brigg Institute (JBI) critical appraisal checklist and the quality of citizen science research using the Citizen Science Appraisal Tool. Results: Citizen science studies in nursing were notably recent (2017-2023). Five research areas were identified, with environmental health being the most predominant. Multiple tools, both technological and traditional, were utilized, with the "Photovoice" and "Our Voice" methodologies being prominent. Citizen participation was limited to data collection and analysis in 7 out of the 13 studies, with most studies working with small samples. Findings regarding the application of this practice were positive, but no study exceeded 26 points on the CSAT scale to be considered high quality in citizen science. Conclusions: Citizen science can be a promising approach within the field of nursing. There is a need to increase individual participation to fully realize the potential bidirectional benefits. It is imperative to establish a common theoretical framework and continue working on the development of this methodology within nursing.